2022
DOI: 10.1007/s00210-022-02251-1
|View full text |Cite
|
Sign up to set email alerts
|

Guanabenz—an old drug with a potential to decrease obesity

Abstract: The aim of this study was to determine, in the diet-induced obesity model in rats, the potential of Guanabenz to reduce body weight and ameliorate some metabolic disturbances. Obesity was induced in rats by a high-fat diet. After 10 weeks, rats were treated intraperitoneally with Guanabenz at the two doses: 2 or 5 mg/kg b.w./day, once daily for 25 days. The spontaneous activity of rats was measured for 24 h on the 1st and 24th day of the Guanabenz treatment with a special radio-frequency identification system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Our studies did not indicate significant differences in the effect on core body temperature between the control and 4-OH-Guanabenz groups. This is another difference between 4-OH-Guanabenz and guanabenz, since the latter significantly lowered the core body temperature of rats, as we showed in our previous study [ 18 ].…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Our studies did not indicate significant differences in the effect on core body temperature between the control and 4-OH-Guanabenz groups. This is another difference between 4-OH-Guanabenz and guanabenz, since the latter significantly lowered the core body temperature of rats, as we showed in our previous study [ 18 ].…”
Section: Discussionsupporting
confidence: 56%
“…In our previous studies, we have shown that guanabenz supports weight loss and ameliorates some metabolic disorders in obese animals [ 18 ]. In this study, we decided to test its metabolite in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations